LEVEL OF COMMUNITY PARTICIPATION IN MANAGEMENT OF URBAN FOREST OF THE NATIONAL WIRAKARYA CAMPING IN BONGOHULAWA, GORONTALO REGENCY - Manyo'e, Endi Triyanto; Sulila, Ismet (Public Policy Journal, 2022)
The efforts of the central and regional governments in managing urban forests should also be encourage participation from the community which is carried out starting from the planning stage, the stage of maintaining protection and security, the stage of utilization as well as the stage of monitoring and evaluation. This research was conducted with the aim of knowing the level of community participation in the management of the Bongohulawa National Wirakarya Camping City Forest in Gorontalo Regency. The research design used is descriptive quantitative research using survey methods. The survey method was carried out by distributing questionnaires with a closed question model that was posed to the respondents by purposive sampling.Â The average level of community participation at the planning and monitoring evaluation stages is in the low category. Meanwhile, the average level of participation at the maintenance, protection and security stage as well as at the utilization stage is in the medium category.